2021
DOI: 10.3389/fonc.2021.652458
|View full text |Cite
|
Sign up to set email alerts
|

Exploratory Study of the Clinical Value of Near-Infrared Sentinel Lymph Node Mapping With Indocyanine Green in Vulvar Cancer Patients

Abstract: BackgroundThis study aimed to evaluate the clinical value of indocyanine green sentinel lymph node (SLN) mapping in patients with vulvar cancer. The conventional procedure of SLN mapping in vulvar cancer includes peritumoral injection of technetium-99m nanocolloid before surgery and intraoperative injection of a blue dye. However, these techniques harbor some limitations. Near-infrared fluorescence imaging with indocyanine green has gained popularity in SLN mapping in different types of cancer.MethodsWe analyz… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 38 publications
(39 reference statements)
0
6
0
Order By: Relevance
“…To be able to more accurately detect the amount of SLN and its anatomical location, a preoperative 3D single-photon emission tomography imaging is performed [ 115 ]. However, this technique consists of some limitations: (i) preoperative injection of radiopharmaceuticals is a painful procedure; (ii) blue dye can cause allergic reactions and stain at the injection site; and, (iii) when the lymphatic tissue is covered by skin or fat the visualization of blue dye is limited, resulting in a lower detection rate [ 116 ].…”
Section: Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…To be able to more accurately detect the amount of SLN and its anatomical location, a preoperative 3D single-photon emission tomography imaging is performed [ 115 ]. However, this technique consists of some limitations: (i) preoperative injection of radiopharmaceuticals is a painful procedure; (ii) blue dye can cause allergic reactions and stain at the injection site; and, (iii) when the lymphatic tissue is covered by skin or fat the visualization of blue dye is limited, resulting in a lower detection rate [ 116 ].…”
Section: Treatmentmentioning
confidence: 99%
“…In patients with lymph node metastasis or lymphatic vascular space invasion, ICG was significantly higher than TC-99 ( p = 0.035 and 0.004, respectively). Finally, the authors concluded that SLN mapping using ICG with near-infrared fluorescence imaging in patients with vulvar cancer is feasible, accurate, and safe [ 116 ].…”
Section: Treatmentmentioning
confidence: 99%
“…In addition, fluorescence-emission-guided tissue observation can detect small and numerous lymph nodes. This approach offers the advantage of swiftly observing these nodes during the surgical procedure [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Based on this evidence, this technique has been extended to vulvar cancers. Recently, several studies have shown the feasibility, accuracy, and safety of SLN mapping using ICG with near-infrared fluorescence imaging in vulvar cancer [ 7 , 8 ].…”
mentioning
confidence: 99%
“…The advantages of SLN mapping using ICG with near-infrared fluorescence imaging include easier application, absence of radioactivity, and fewer side effects [ 8 ]. In addition, the procedure is less invasive, with little pain and scarring.…”
mentioning
confidence: 99%